Linux Cookbook, 2nd Edition - Schroder, Carla (O'Reilly Media, Incorporated, 2021)
This handy cookbook teaches new-to-intermediate Linux users the essential skills necessary to manage a home or small business network. All of the recipes in this book are useful for any Linux system, including local area networks that involve iOS- or Android-powered devices. You'll learn how to install, maintain, and troubleshoot a Linux system, add and remove software, manage filesystems, run backups, and more. Carla Schroder, author of over a thousand Linux how-tos for various publications, teaches you the solid Linux foundations you need to build and run your network. How do you multiboot? Or troubleshoot software, hardware, and network issues? Each recipe addresses a specific problem and includes a discussion that explains the solution and provides insight into how it works. Learn how the Linux ecosystem is structured Set up a local area network (LAN) Enable smartphones and tablets to safely connect to your LAN Manage fundamental subsystems and essential tasks Secure remote access and build a firewall/internet gateway Manage users and groups, and filesystems and partitions Rescue nonbooting systems Manage name services and the Dynamic Host Configuration Protocol (DHCP).